STRATEGY FOR ENFORCING THE KPK EMPLOYEE CODE OF ETHICS AND CONDUCT: LESSONS FROM INTERNATIONAL BEST PRACTICES - Rina Martina Puspitasari; Hidayaturahmi Hidayaturahmi (DIA: Jurnal Administrasi Publik, 2026)
The enforcement of ethical codes and behavior within law enforcement agencies is crucial to ensuring the integrity and accountability of these institutions, particularly in the Corruption Eradication Commission (KPK). Although KPK has established an ethical code, there are challenges related to the independence of the institution, transparency in supervision, and whistleblower protection, which can diminish the effectiveness of the enforcement of the ethical code. This article aims to analyze the ethical code enforcement systems in three countries with effective anti-corruption systems: Singapore, Canada, and Finland, and how these principles can be applied in the context of KPK. The study finds that the independence of supervisory bodies, transparency in the supervision process, whistleblower protection, and independent audits are key factors in the success of ethical code enforcement in these countries. Based on these findings, this article recommends that KPK strengthen the independence of its Supervisory Board, improve transparency in investigation processes, and adopt a stronger whistleblower protection system. Additionally, KPK should implement independent audits conducted regularly to enhance accountability and strengthen public trust in the institution. By adapting these elements, KPK can improve the effectiveness of law enforcement and achieve a more sustainable goal of corruption eradication in Indonesia.